An assessment of the state of nature in the United Kingdom: A review of findings, methods and impact. (November 2018) - Burns, F.; Eaton, M.A.; Hayhow, D.B.; Outhwaite, C.L.; Al Fulaij, N.; August, T.A.; Boughey, K.L.; Brereton, T.; Brown, A.; Bullock, D.J.; Gent, T.; Haysom, K.A.; et al.
Highlights: A clear overview of biodiversity status is needed to allow informed decision making. We used a range of types of species status data to create three biodiversity metrics. The metrics were populated with data for a broad range of taxonomic groups in the UK. We explore reducing residual taxonomic bias and improving these and similar metrics. Abstract: Clear, accessible, objective metrics of species status are critical to communicate the state of biodiversity and to measure progress towards biodiversity targets. However, the population data underpinning current species status metrics is often highly skewed towards particular taxonomic groups such as birds, butterflies and mammals, primarily due to the restricted availability of high quality population data. A synoptic overview of the state of biodiversity requires sampling from a broader range of taxonomic groups. Incorporating data from a wide range of monitoring and analysis methods and considering more than one measure of species status are possible ways to achieve this. Here, we utilise measures of species' population change and extinction risk to develop three species status metrics, a Categorical Change metric, a Species Index and a Red List metric, and populate them with a wide range of data sources from the UK, covering thousands of species from across taxonomy. The species status metrics reiterate the commonly reported decline in freshwater and terrestrial species' status in the UK in recent decades and give little evidence that this rate of decline has slowed. The utility of species status metrics is further improved if we can extrapolate beyond the species sampled to infer the status of the community. For the freshwater and terrestrial species status metrics presented here we can do this with some confidence. Nevertheless, despite the range and number of species contributing to the species metrics, significant taxonomic bias remained and we report weighting options that could help control for this. The three metrics developed were used in the State of Nature 2016 report and indications are they reached a large number of audience members. We suggest options to improve the design and communication of these and similar metrics in the future.